Lewis Acid Accelerated Aryl Ether Bond Cleavage with Nickel: Orders of Magnitude Rate Enhancement Using AlMe3. Issue 48 (18th October 2016) - Kelley, Paul; Edouard, Guy A.; Lin, Sibo; Agapie, Theodor
Abstract: Study of the kinetics of intramolecular aryl ether C−O bond cleavage by Ni was facilitated by access to a family of metal complexes supported by diphosphines with pendant aryl‐methyl ethers. The nature of the aryl substituents was found to have little effect on the rate of cleavage. In contrast, soluble Lewis acidic additives accelerate the aryl ether cleavage dramatically. The effect of AlMe3 was studied in detail, and showed an increase in rate by several orders of magnitude. Low temperature NMR spectroscopy studies demonstrate quantitative coordination of ether to Al. From the Lewis acid‐bound precursor, the activation parameters for ether cleavage are significantly lower. These findings provide a mechanistic basis for milder catalyst design for the activation of strong bonds. Abstract : Study of the kinetics of intramolecular aryl ether C−O bond cleavage by Ni was facilitated by access to a family of metal complexes supported by diphosphines with pendant aryl‐methyl ethers. The nature of the aryl substituents was found to have little effect on the rate of cleavage. In contrast, soluble Lewis acidic additives accelerate the aryl ether cleavage dramatically. The effect of AlMe3 was studied in detail, and showed increase in rate by several orders of magnitude.